2015
DOI: 10.1242/jcs.166009
|View full text |Cite
|
Sign up to set email alerts
|

Induction of stable ER–plasma-membrane junctions by Kv2.1 potassium channels

Abstract: Junctions between cortical endoplasmic reticulum (cER) and the plasma membrane are a subtle but ubiquitous feature in mammalian cells; however, very little is known about the functions and molecular interactions that are associated with neuronal ER-plasma-membrane junctions. Here, we report that Kv2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
166
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(176 citation statements)
references
References 47 publications
10
166
0
Order By: Relevance
“…Previous studies in HEK293 cells have suggested that most if not all of the Kv2.1 channels clustered at PM:ER MCS may be non-functional (74). Taken together with the finding that Kv2.1 stabilizes and/or enhances PM:ER MCS, as shown here in M phase COS-1 cells, and previously in HEK293 cells and neurons (12,23) suggests a structural, rather than ion conducting, role for Kv2.1 at these sites. As tools to study functions of ion channel proteins outside of their ionic conductance advance, a theme whereby ion channels have functions supplementary to transmembrane ion flux has begun to emerge, for example, serving as PM scaffolding proteins for intracellular signaling complexes (75).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Previous studies in HEK293 cells have suggested that most if not all of the Kv2.1 channels clustered at PM:ER MCS may be non-functional (74). Taken together with the finding that Kv2.1 stabilizes and/or enhances PM:ER MCS, as shown here in M phase COS-1 cells, and previously in HEK293 cells and neurons (12,23) suggests a structural, rather than ion conducting, role for Kv2.1 at these sites. As tools to study functions of ion channel proteins outside of their ionic conductance advance, a theme whereby ion channels have functions supplementary to transmembrane ion flux has begun to emerge, for example, serving as PM scaffolding proteins for intracellular signaling complexes (75).…”
Section: Discussionsupporting
confidence: 85%
“…Cortical ER Morphology-Kv2.1 clusters are localized to PM:ER MCS in neurons (11)(12)(13)(14) and when heterologously expressed in HEK293 cells (23), where they induce PM:ER MCS formation (23). The ability of Kv2.1 to induce and/or stabilize PM:ER MCS in neurons and HEK293 cells depends on the localization of Kv2.1 to clusters, as acutely disrupting Kv2.1 clusters pharma- cologically or with mutations blocks the effect of Kv2.1 on PM:ER MCS (23).…”
Section: Phase Kv21 Clusters Are Located At Pm:er Mcs and Altermentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting aspect of the Kv2.1 channel localization is its close association with subsurface cisternae (Fox et al, 2013a, 2015)—intracellular ER-derived membranes—that buffer and store intracellular calcium necessary for propagation of signaling cascades important for the regulation of neuronal trafficking (Figure 2C). Subsurface cisternae are called cortical endoplasmic reticulum (cER) and are suggested to form a hub that supports the trafficking of plasma membrane proteins (Fox et al, 2013a).…”
Section: Segregated Distribution Of Vgcs In Dendritesmentioning
confidence: 99%